Response of urea and growth regulators on bearing and quality of "Amrapali" mango - Mandal, Bipul Kumar; Ray, R.N; Prasad, K.K. (Annals of Agricultural Research, 2014)
To assess the impact of foliar spray of urea (2 %), thio-urea (1000 ppm), and PGRs (GA3 100ppm, NAA 40 ppm, ethephon 200 ppm, SA 100 and 200 ppm and triadimefon 1000 and 2000 ppm) alone and incombination with urea 2% on bearing and fruit quality of Amrapali mango under agro-climatic condition of Ranchi were carried out at the Department of Horticulture, Birsa Agriculture University, Jharkhand during two fruiting season experiments 2008-2010. Maximum duration of panicle emergence (37 days) and minimum days required for anthesis (19.33 days) were observed from ethephon 200 ppm treated tree. However, increased intensity of flowering shoot (88.50%) and maximum fruit retention per panicle (5.41%) were observed with SA 100ppm in combination with urea spray over control (water spray). The highest yield per tree (16.21 kg) was recorded under plant treated with SA 200 ppm in combination with urea 2 percent. The highest total sugar (11.97%) as well as non reducing sugar (9.51%)were estimated in the fruits of the plant sprayed with triadimefon 200 ppm. While, the highest increase in ascorbic acid and Î²-carotene were measured from the fruits of the plant sprayed with triadimefon 2000 ppm in combination with urea 2 percent. Beside these, salicylic acid 100 ppm along with urea 2 percent recorded minimum spoilage (10.62%) over control.